Assessing the impact of health financing on health outcomes in Zimbabwe: (1990-2023) - Musariri, Yeukai (BUSE, 2024)
This study is premised on exploring the existing relationship between health financing, under five mortality and infant mortality rates in Zimbabwe between 1990 and 2023. The study employed advanced econometric techniques, including Vector Auto regression (VAR) modeling, Impulse Response Function (IRF) analysis, and Forecast Error Variance Decomposition (FEVD) analysis, using Stata version 14.0. The empirical results reveal several critical findings. Firstly, health financing has a significant positive impact on reducing under-five and infant mortality rates in Zimbabwe. Increased health financing leads to decreased mortality rates, emphasizing the critical role of health financing in improving health outcomes. Secondly, the study reveals a positive relationship between population density and mortality rates, highlighting the need for targeted interventions addressing population density-related challenges. The study strongly recommends authorities to prioritize increasing health financing to support healthcare programs targeting underfive and infant mortality. Also, implementing long-term health financing strategies and enhancing infrastructure and human resources is critical for ensuring sustained impact, in line with the systems thinking approach. Furthermore, addressing population density-related challenges through urban planning, community-based healthcare, and family planning services is essential.
Keywords: Health Financing Mechanisms; Health System Outcomes; Macro-factors; Zimbabwe